Implementasi Media Puzzle Untuk Meningkatkan Minat Belajar Siswa pada Mata Pelajaran IPAS di SDN Mlatiharjo 02 Semarang - Dwi Kartikasari; Endang Wuryandini; Muhamad Nurodin (Departement of Mathematics Education, 2024)
The aim of this research is to describe the implementation of puzzle media to increase students' interest in learning in science and science subjects at SDN Mlatiharjo 02 Semarang. This type of research is descriptive qualitative. The subjects in this research were 26 VB class students. The method used in this research is by collecting data through observation, interviews, and documentation. The results of the research show that the implementation of puzzle media to increase students' interest in learning in science and science subjects at SDN Mlatiharjo 02 Semarang showed results of 88 percent classified as very high interest in learning criteria